The grison, Galictis vitatta (Carnivora: Mustelidae) in coffee agroecosystems, Costa Rica (UNED Research Journal, 2022)
Introduction: The grison, Gallictis vittata, is a IUCN species of least concern. However, in Mesoamerican countries it is rare and probably endangered, and studies are scarce. Objective: To report G. vitatta in a new habitat. Methods: We placed four camera traps in strategic places such as food sources, burrows, water bodies forest ecotone in Alajuela, Costa Rica. Results: We obtained two records of G. vittata in the transition between coffee plantation and secondary forest. Conclusion: These records expand the known range of G. vittata and provide information for its conservation.
Keywords: Greater grison, trap camera, carnívora, mustelid.